IDENTIFIKASI KEJADIAN KETUBAN PECAH DINI (KPD) DI RSIA DIAN PERTIWI KABUPATEN KARANGANYAR TAHUN 2022 - Suwarnisih, Suwarnisih; Anggraini, Yeni (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
ABSTRACT. The cause of maternal mortality in Indonesia is not only due to direct causes such as bleeding, infection, pre eclampsia, but there are also other indirect factors that contribute greatly to increasing the risk of maternal death (PP IBI, 2016). Premature rupture of membranes is when the amniotic membranes rupture before there are signs of labor and wait one hour before labor occurs (Manuaba, 2009). According to Manuaba, 2007, the causes of premature rupture of membranes include: multipara, grandemultipara, hydramnios, positional abnormalities (latitudinal, breech), CPD, multiple pregnancies, hanging stomach. The aim of this research is to determine the incidence of KPD at RSIA Dian Pertiwi, Karanganyar district. Descriptive observational research method. The population in this study was 32 people. The sampling technique used was